Overview of glycemic control among admitted patients with diabetes in Tripoli University Hospital - Alshwikh, Haifa Elhadi; Hander, Faiza (Journal of Cardiology and Cardiovascular Medicine, 2022)
Aim: To examine the relationship between the levels of HbA1c and hospital admission rates. Methods: We recorded HbA1c levels of all diabetic patients in Tripoli University Hospital over one year. Results: The mean HbA1c was 8.03%, with no difference between males and females. Over half of patients (56.5%) were admitted through their diabetes was well-controlled. Over half of the patients with type 1 diabetes (57/102, 55.9%) had a high HbA1c at admission compared to 42.1% of patients with type 2, who were mainly admitted with HbA1c level within the acceptable range set for this study. The HbA1c level was positively and significantly correlated with the length of hospital stay (R = 0.93, p = 0.000), and was significantly associated with hyperglycemia, diabetic ketoacidosis, coronary artery disease, limb ischemia, cataract, osteomyelitis, and non-alcoholic steatohepatitis. Conclusion: HbA1c is correlated significantly with hospitalization in type 1 diabetes but not in type 2.